Family Policy Changes at the Micro-Level in Sweden and Finland during the 1990s - Heikki Hiilamo (Luxembourg Income Study (LIS), 2002)
Up to the 1990s the development of family policy was an integral part of the success story of the Nordic welfare state. This article aims to evaluate the impact of legislative amendments to family policy at the micro-level in Sweden and Finland during the 1990s. We follow the micro-level development of family policy and assess whether the changes in family policy during the 1990s led Finland and Sweden away from the Nordic model.
Keywords: 330; Familienpolitik; Soziale Sicherheit; Mikroökonomische Fundierung; Finnland; Schweden